A novel grid-net design to eliminate bycatch in beam trawl fishing for the veined rapa whelk in the south-eastern Black Sea - ERYAŞAR, AHMET RAIF (Mediterranean Marine Science, 2018)
Beam trawl fisheries in the Black Sea target the veined rapa whelk (Rapana venosa) while other species of fish and crabs are re-turned to the sea dead or alive. Smaller bivalves and crabs are also packed with the catch without elimination. In this study, novel grid-net designs (GNDs) with two different bar spacings were tested to reduce the bycatch. Thirty hauls (15 hauls for each bar spacing) were carried out in the south-eastern Black Sea between 17 and 26 August 2017. Bycatch compositions were compared by towing a commercial diamond mesh and one of the grid-net beam trawls simultaneously onboard a commercial vessel. There were statistically significant (p<0.01, 78% and 83%) decreases in the mean bycatch weight for 20 mm and 30 mm grid-nets, respectively. The estimated commercial loss was 14% in the 20 mm GND and 39% in the 30 mm GND in the landing values as compared to the commercial gear. In conclusion, the use of grid-net design for beam trawl fishing in the south-eastern Black Sea can significantly reduce the bycatch of most benthic species. There is a trade-off between the reduction in the bycatch and some commercial loss, which could be offset with some compensation to fisheries, such as an extension of the fishing season.